Pengaruh Social Comparison Terhadap Body Esteem Pada Remaja Wanita Pengguna Instagram - Bahrudin, Bahrudin; Arkam, Saiful (Jurnal Syntax Fusion, 2023)
This article is gonna delve on how much social comparison can affect body esteem on adolescent women that is actively using Instagram. The samples consist of 145 women aged between 18-25 years old in Jabodetabek area who are currently an active Instagram users. The research will be done using the quantitative approach that will study social comparison as the independent variable, using the Upward and Downward Physical Appearance Comparison Questionnaire and body esteem as the dependent variable, using the Body Esteem Scale – Revised. This study is gonna examine the effect of social comparison on adolescent woman’s body esteem and how differing types of social comparison (upward & downward) can affect different aspect of body esteem (sexual attractiveness, weight concern & physical condition) on a subject that actively uses Instagram. This study found that social comparison negatively contributes 32.5% upon woman’s body esteem, thus confirm the hypotheses that social comparison have a significant effect on adolescent women’s body esteem. But on the other side, found that downward social comparison does reflect positively on woman’s body esteem.